UPAYA PENURUNAN POTENSI KERAWANAN LINGKUNGAN MELALUI PEMASANGAN PAGAR PENGAMAN DI DESA NGENEP KEC. KARANGPLOSO KAB. MALANG - Nurhadi, Nurhadi; Walid, Achmad; Farida, Nike Nur; Monasari, Ratna; Aji, Supa Kusuma; Winoko, Yuniarto Agus (Universitas Mataram, 2025)
RT 04 RW 16, Ngenep Village, Karangploso District, Malang Regency faces environmental vulnerability due to a damaged security fence, allowing outsiders to enter and exit freely, increasing the risk of safety disturbances. This problem is worsened by the fact that the housing estate management was abandoned after the developer was declared bankrupt, forcing residents to manage the environment independently. This situation raises concerns about neighborhood security and urges the need for a concrete, collective solution to mitigate the issue. This community service activity aims to reduce environmental vulnerability by designing and constructing a permanent safety fence in a vacant lot prone to security risks as a preventive measure to enhance neighborhood safety. The methods include analyzing the partner's problems, determining priority issues, designing the fence using AutoCAD, and constructing a 7 x 3.25-meter fence consisting of stone foundations, cast pillars, and lightweight brick walls. The results showed that the safety fence was successfully installed as planned, serving as a physical barrier that limits outsider access, enhances residents' sense of security, and fosters community awareness regarding environmental safety. An evaluation of the project revealed a cost efficiency of 17% compared to the initial Budget Plan (RAB). This activity is expected to serve as a practical solution model for other areas facing similar challenges in community-based environmental security management. Moreover, this project has had a positive impact by increasing community solidarity and encouraging a spirit of mutual cooperation among residents to protect their neighborhood environment.